2016
DOI: 10.1039/c6cc00273k
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of design strategies for α-helix backbone modification in a protein tertiary fold

Abstract: We report here the comparison of five classes of unnatural amino acid building blocks for their ability to be accommodated into an α-helix in a protein tertiary fold context. High-resolution structural characterization and analysis of folding thermodynamics yield new insights into the relationship between backbone composition and folding energetics in α-helix mimetics and suggest refined design rules for engineering the backbones of natural sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 44 publications
2
49
0
Order By: Relevance
“…Taking the energetic values for 1 as a baseline (Figure 7), the backbone modifications in 4 (2 α→N-Me-α; 4 α→β 3 ) have a moderately unfavorable effect on folding ΔH (~0.6 kcal mol −1 per substitution) that is more than compensated for by a favorable effect on folding TΔS (~0.7 kcal mol −1 per substitution). The above qualitative trend follows that seen upon α→β 3 modifications in the helix of GB1; 16a however, the quantitative balance between parameters differs between the two systems. 5d The magnitude of the unfavorable ΔΔH in 4 vs. 1 is comparable in GB1 and Sp1–3 yet the corresponding favorable ΔΔS is much greater in the zinc finger motif.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…Taking the energetic values for 1 as a baseline (Figure 7), the backbone modifications in 4 (2 α→N-Me-α; 4 α→β 3 ) have a moderately unfavorable effect on folding ΔH (~0.6 kcal mol −1 per substitution) that is more than compensated for by a favorable effect on folding TΔS (~0.7 kcal mol −1 per substitution). The above qualitative trend follows that seen upon α→β 3 modifications in the helix of GB1; 16a however, the quantitative balance between parameters differs between the two systems. 5d The magnitude of the unfavorable ΔΔH in 4 vs. 1 is comparable in GB1 and Sp1–3 yet the corresponding favorable ΔΔS is much greater in the zinc finger motif.…”
Section: Resultssupporting
confidence: 59%
“…We recently reported a stabilizing effect from β 3 →C α -Me-α substitution in the helix of the GB1 tertiary fold and were motivated to see to what degree those observations might hold in a different structural context. 16b The data obtained in the Co 2+ binding assay showed that peptide 9 supports a metal coordination environment indistinguishable from both analogue 4 and the native backbone ( 1 ). Thus, we advanced peptides 1 , 4 , and 9 to experiments aimed at a more thorough characterization of folded structure and stability.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Significantly, many of these tertiary and quaternary protein structure scaffolds have been engineered for phage display, allowing rapid selection of potent sequences for desired targets. Synthetic protein tertiary structures with non-natural backbones have also been described[110-112]. …”
Section: Fragment-based Designmentioning
confidence: 99%